RAmbler resolves complex repeats in human Chromosomes 8, 19, and X - Chakravarty, Sakshar; Logsdon, Glennis; Lonardi, Stefano

(untitled) (Genome Research, 2025)
Repetitive regions in eukaryotic genomes often contain important functional or regulatory elements. Despite significant algorithmic and technological advancements in genome sequencing and assembly over the past three decades, modern de novo assemblers still struggle to accurately reconstruct highly repetitive regions. In this work, we introduce RAmbler (Repeat Assembler), a reference-guided assembler specialized for the assembly of complex repetitive regions exclusively from Pacific Biosciences (PacBio) HiFi reads. RAmbler (1) identifies repetitive regions by detecting unusually high coverage regions after mapping HiFi reads to the draft genome assembly, (2) finds single-copy k-mers from the HiFi reads, (i.e., k-mers that are expected to occur only once in the genome), (3) uses the relative location of single-copy k-mers to barcode each HiFi read, (4) clusters HiFi reads based on their shared barcodes, (5) generates contigs by assembling the reads in each cluster, and (6) generates a consensus assembly from the overlap graph of the assembled contigs. Here, we show that RAmbler can reconstruct human centromeres and other complex repeats to a quality comparable to the manually curated Telomere-to-Telomere human genome assembly. Across more than 250 synthetic data sets, RAmbler outperforms hifiasm, LJA, HiCANU, and Verkko across various parameters such as repeat lengths, number of repeats, heterozygosity rates, and depth of sequencing.